Noncoding RNAs in liver cancer stem cells: The big impact of little things. (1st April 2018) - Lv, Hongwei; Lv, Guishuai; Han, Qin; Yang, Wen; Wang, Hongyang
Abstract: The high rate of recurrence and heterogeneity make hepatocellular carcinoma (HCC) as one of the most prevalent malignancy worldwide. Cancer stem cells (CSCs), also known as tumor-initiating cells, are responsible for cancer initiation, metastasis, drug resistance and relapse, accounting for the heterogeneous and hierarchical organizations of HCC. Therefore, CSCs are novel targets for more efficient liver cancer therapies. New data continues to mount on the functions of noncoding RNAs in multiple processes of liver CSCs, including malignant proliferation, self-renewal, tumorigenicity, and survival. Thus, it is highly critical to develop improved understanding of the mechanisms by which noncoding RNAs control CSCs functions for developing better diagnostic and therapeutic strategies. Herein, we will shed light on the regulatory roles of noncoding RNAs, especially microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), in liver CSCs acquisition and maintenance after presenting an overview about the characteristics of liver CSCs and their origins.